Resilience and social support as pathways to academic achievement and adjustment among international students at a Pakistani university - Hafiza Aqsa, (Journal of International Students, 2026)
International students often experience challenges when adapting to academic systems and cultural settings different from their own. Grounded in Bandura’s social cognitive theory, this study examined the role of resilience and social support in predicting academic achievement and adjustment among international students at the University of the Punjab, Lahore, Pakistan. A purposive sample of 100 international students (M = 23.36 years, SD = 3.47) participated in the study. The results indicated that resilience and social support were significant positive predictors of adjustment, whereas the length of stay in Pakistan positively predicted academic achievement. Compared with female students, male students reported higher levels of social support from significant others and family.